Prevalence, genomic characterization and antimicrobial resistance of Campylobacter spp. isolates in pets in Shenzhen, China - Ju, Changyan; Ma, Yanping; Zhang, Bi; Zhou, Guilan; Wang, Hairui; Yu, Muhua; He, Jiaoming; Duan, Yongxiang; Zhang, Maojun (Frontiers in Microbiology, 2023)
Abstracts: The prevalence of Campylobacter spp. in pets is a potential concern for human health. However, little is known about the pet-related Campylobacter spp. in China. A total of 325 fecal samples were collected from dogs, cats, and pet foxes. Campylobacter spp. were isolated by culture, and MALDI-TOF MS was used to identify 110 Campylobacter spp. isolates in total. C. upsaliensis (30.2%, 98/325), C. helveticus (2.5%, 8/325), and C. jejuni (1.2%, 4/325) were the three found species. In dogs and cats, the prevalences of Campylobacter spp. were 35.0% and 30.1%, respectively. A panel of 11 antimicrobials was used to evaluate the antimicrobial susceptibility by the agar dilution method. Among C. upsaliensis isolates, ciprofloxacin had the highest rate of resistance (94.9%), followed by nalidixic acid (77.6%) and streptomycin (60.2%). Multidrug resistance (MDR) was found in 55.1% (54/98) of the C. upsaliensis isolates. Moreover, 100 isolates, including 88 C. upsaliensis, 8 C. helveticus, and 4 C. jejuni, had their whole genomes sequenced. By blasting the sequence against the VFDB database, virulence factors were identified. 100% of C. upsaliensis isolates carried the cadF, porA, pebA, cdtA, cdtB, and cdtC genes. The flaA gene was present in only 13.6% (12/88) of the isolates, while the flaB gene was absent. By analyzing the sequence against the CARD database, we found that 89.8% (79/88) of C. upsaliensis isolates had antibiotic target alteration in the gyrA gene conferring resistance to fluoroquinolone, 36.4% (32/88) had the aminoglycoside resistance gene, and 19.3% (17/88 ) had the tetracycline resistance gene. The phylogenetic analysis using the K-mer tree method obtained two major clades among the C. upsaliensis isolates. All eight isolates in subclade 1 possessed the gyrA gene mutation, the aminoglycoside and tetracycline resistance genes, and were phenotypically resistant to six classes of antimicrobials. This study is the first to have documented the presence of Campylobacter spp. in pets in Shenzhen, China. In this work, C. upsaliensis of subclade 1 required additional attention due to its broad MDR phenotype and relatively high flaA gene prevalence.